Hygienic-dietary recommendations for major depression treatment: Study protocol of a randomized controlled trial - Garcia-Toro Mauro; Roca Miquel; Monzón Saray; Vives Margalida; Oliván Bárbara; Vicens Enric; Salva Joan; Gili Margalida (BMC Psychiatry, 2012)
Abstract Background Depression is a highly prevalent and disabling mental disorder with an incidence rate which appears to be increasing in the developed world. This fact seems to be at least partially related to lifestyle factors. Some hygienic-dietary measures have shown their efficacy as a coadjuvant of standard treatment. However, their effectiveness has not yet been proved enough in usual clinical practice. Methods Multicenter, randomized, controlled, two arm-parallel, clinical trial involving 300 patients over 18 years old with a diagnosis of Major Depression. Major depression will be diagnosed by means of the Mini-International Neuropsychiatric Interview. The Beck Depression Inventory total score at the end of the study will constitute the main efficacy outcome. Quality of Life and Social and Health Care Services Consumption Scales will be also administered. Patients will be assessed at three different occasions: baseline, 6-month follow-up and 12-month follow-up. Discussion We expect the patients in the active lifestyle recommendations group to experience a greater improvement in their depressive symptoms and quality of life with lower socio-sanitary costs. Trial registration ISRCTN73931675